Penggunaan Media Sosial Sebagai Simbol dalam Mendukung Hubungan LGBT - Edward Charitoun Sarmawando Gawa; Valentya Te’dang (Departement of Mathematics Education, 2023)
The story of Romeo and Juliet is a motivating story about the meaning of a love between lovers, where there is loyalty instilled until the end of their lives. Surely this story has become a pioneer of true love in various parts of the world. However, we need to know that this story is very gripping because the basically want to do marriage but not approved. The rejection made the couple mistake that they would live together forever by ending their lives. Establishing a relationship in today's era is not difficult, but it is even more adequate because of technological sophistication, social media is the work of technological developments. The use of social media in finding a partner has been intensively carried out in the social 5.0 era. this cannot be denied that LGBT people also do that, but seeing that these people have not been fully accepted by society, are there any other social media they use. Therefore the author will review social media which is a symbol in supporting the relationship of LGBT couples.